Influência da temperatura na infecção de tilápias do nilo por streptococcus agalactiae - Marcusso, Paulo Fernandes [UNESP]; Aguinaga, Jefferson Yunis [UNESP]; Da Silva Claudiano, Gustavo [UNESP]; Eto, Silas Fernandes [UNESP]; Fernandes, Dayanne Carla [UNESP]; Mello, Hurzana [UNESP]; De Almeida Marinho Neto, Fausto; Salvador, Rogério; De Engrácia Moraes, Julieta Rodini [UNESP]; De Moraes, Flávio Ruas [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2015)
Environmental changes affect fish homeostasis, turning them more susceptible to diseases. In Brazil, outbreaks of Streptococcus agalactiae infection have been reported in Nile tilapia when they are outside of their thermal comfort zone. This investigation evaluated mortality rate and which were the most infected organs at temperatures that naturally occurred in southern of Brazil. Forty Nile tilapia (Oreochromis niloticus) were infected with S. agalactiae and distributed in four groups (n=10) and each group was exposed to a different temperature: G1: 24°C, G2: 26°C, G3: 28°C, and G4: 32°C. Fish were monitored for 10 days. In this period, fish that presented irreversible clinical signs were sacrificed and samples of brain, liver, and kidney were collected for bacteriological and molecular analysis. Signs compatible with a streptococcal infection were observed in all groups. Highest mortality rates occurred at 24°C and 32°C. The brain was the most affected organ with the highest percentage of isolation of S. agalactiae by both methods of diagnosis. The results suggest that, as in mammals, temperatures that are further away from the comfort zone influence fish homeostasis, increasing susceptibility to bacterial infections.
Influence of temperature on streptococcus agalactiae infection in nile tilapia
Keywords: Homeostasis; Oreochromis niloticus; Teleost; Thermal stress